Determination of the iron bioavailability, conformation, and rheology of iron‐binding proteins from Tegillarca granosa. Issue 1 (28th October 2020) - Li, Gaoshang; Zhan, Junqi; Xu, Anqi; Tan, Beibei; Sun, Nan; Wang, Chen; Jia, Ru; Li, Chao; Zhang, Jinjie; Yang, Wenge
Abstract: The increased interest in achieving, solely through diet, the same effect on iron levels with supplementation, leads to numerous studies on iron absorption of iron binding proteins (IBPs). The characteristics of IBPs from Tegillarca granosa ( T. granosa ) and its iron utilization were determined to analyze their relationship. The results showed in T. granosa, Fe(ӀӀ) was main iron form in hemoglobin (TH) and that Fe(ӀӀ) and Fe(ӀӀӀ) coexisted in ferritin (TF). After in vitro digestion, TH was easier to be digested than TF, bovine hemoglobin, and bovine ferritin. In caco‐2 cells model, iron bioavailability of TH also was the best, which related to TH's superior fluid properties, higher ratios of α‐helix to β‐sheet and amide I to amide II. These suggest TH could be used as a good source of organic iron and provide references for application of T. granosa in human nutrition. Practical applications: This research investigated the iron bioavailability and structural properties of iron‐binding proteins from Tegillarca granosa ( T. granosa ). Moreover, the effects of iron absorption in bovine hemoglobin and ferritin were compared with those from T. granosa . The results showed the hemoglobin in T. granosa had better iron bioavailability and it could be a good source of iron. These data could provide a basic instruction of the application of T. granosa in functional food production. Abstract : This research investigated the iron bioavailability and structural properties of iron‐binding proteins (hemoglobin and ferritin) from Tegillarca granosa ( T. granosa ), finding that Fe(ӀӀ) was main iron form of iron‐binding proteins, and the hemoglobin of T. granosa had better iron digestion and absorption rate, which related to its superior fluid properties, higher ratios of α‐helix to β‐sheet.